Physical and Chemical Characteristics of Green Algae Halimeda opuntia Calcium Powder Extracted Using Hydrochloric Acid - Wijayanti, Ph.D, Ima; Nirwasita, Rania S.; Anggo, Apri D. (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Halimeda opuntia is one of the macroalgae species whose utilization is still slightly known. In the open sea, H. opuntia holds an important role in changing carbon dioxide (CO2) to calcium carbonate (CaCO3). This led to previous research analyzing the calcium content of H. opuntia, which showed 30.30%. However, the information about calcium powder extraction using HCl from H. opuntia has not been reported. This research aimed to observe the physical and chemical characteristics of calcium obtained from H. opuntia extracted using different hydrochloric acid (HCl) concentrations. The method used in this research was experimental laboratories with a completely randomized design (CRD) using different HCl concentrations (1N, 2N, and 3N). The extraction results were analyzed for yield value, moisture, ash, fat, protein, carbohydrate, calcium, color, Scanning Electron Microscope (SEM), particle size, and X-Ray Diffraction (XRD). Data were then analyzed using Analysis of Variance (ANOVA). The use of different HCl concentrations showed significant effect (p0.05) on ash content (91.95±0.47%), carbohydrate content (7.26±0.57%), lightness (L*) (86.21±0.83), yellowness or blueness (b*) (8.81±0.02), E (11.33±0.54), and whiteness index (WI) (83.62±0.70%), where the calcium extracted by 1N HCl (CH1) showed the best result. The SEM microstructural analysis showed a non-porous surface and a single cubical shape in CH1. Diffractogram pattern of calcium extracted from H. opuntia using different concentrations of HCl done by XRD exhibited the same pattern as CaCO3 for all samples. HCl solvent at 1 N can produce calcium powder from H. opuntia with high calcium content and better color characteristics.